Beneficios de la realidad virtual en terapia visual para ambliopía (2021)
Amblyopia is a developmental disorder that limits visual acuity (A.V.) and other binocular functions. Objective: To determine the benefits of virtual reality therapy in patients with amblyopia. Methodology: Narrative review in PubMed, American Academy of Ophthalmology, P.M.C, SciELO, between 2006 and 2021, a total of 36 articles were obtained, 20 were included because they met the inclusion criteria. Results: A.V, stereopsis and suppression are improved with virtual reality therapies in adults, unlike in children who show a lower effect in the treatment compared to traditional methods. Conclusion: The use of this therapy is effective for the treatment of adult patients with amblyopia, mainly of the strabic and anisometropic type, however, it can be effective for children.